Factors Influencing the One- and Two-Year Growth Response in Children Treated with Growth Hormone: Analysis from an Observational Study. (23rd September 2010) - Ross, Judith; Lee, Peter A.; Gut, Robert; Germak, John
Abstract : To assess gender-, pubertal-, age-related differences in change from baseline height standard deviation score (Δ HSDS ), data from 5, 797 growth hormone (GH) naïve pediatric patients (<18 years) with growth hormone deficiency (GHD), multiple pituitary hormone deficiency (MPHD), Turner syndrome (TS), small for gestational age (SGA), Noonan syndrome (NS), and idiopathic short stature (ISS) were obtained from the ANSWER (American Norditropin Studies: Web-enabled Research) Program registry. For patients with SGA, Δ HSDS at year 1 was significantly greater for males versus females (P = .016 ), but no other gender differences were observed. For patients with GHD, Δ HSDS was greater in prepubertal than in pubertal patients. Younger patients for both genders (<11 years for boys; <10 years for girls) showed a greaterΔ HSDS (P < .05 for GHD, MPHD, and ISS). Overall, positiveΔ HSDSs were observed in all patients, with greater growth responses in younger prepubertal children, emphasizing the importance of starting GH treatment early.